2010
DOI: 10.1007/s10552-010-9661-z
|View full text |Cite
|
Sign up to set email alerts
|

Household contact with pets and birds and risk of lymphoma

Abstract: Our results support the hypothesis that early-life exposure to pets, birds and particularly with chickens might be associated with a reduced risk of lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…A previous study, conducted in the Italian center contributing to the present analysis, found a similar protective effect for non‐occupational household contact with poultry starting at age 9 or earlier 13. Here, we explored occupational contact and confirmed the protective effect in the multicenter European study, apparently extended to contact with cattle and swine.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…A previous study, conducted in the Italian center contributing to the present analysis, found a similar protective effect for non‐occupational household contact with poultry starting at age 9 or earlier 13. Here, we explored occupational contact and confirmed the protective effect in the multicenter European study, apparently extended to contact with cattle and swine.…”
Section: Discussionsupporting
confidence: 82%
“…13 Here, we explored occupational contact and confirmed the protective effect in the multicenter European study, apparently extended to contact with cattle and swine. Once divided by lymphoma subtype, age at onset of contact and type of livestock, the number of study subjects in each cell became small.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Another possible explanation for the difference is endotoxin exposure from dogs, since dog ownership has been associated with higher home endotoxin levels [36], and Washington state has the highest prevalence of households with dogs compared to the other study center locations (US Pet Ownership & Demographic Sourcebook, 2007, www.avma.org) (information on dog ownership was not collected in our study). Note that dog ownership has been associated with a decreased NHL risk [37, 38]).…”
Section: Discussionmentioning
confidence: 99%